Macro–Microscopic Mechanical Study of Clay–Structure Interface Shear Behavior Using Direct Shear Testing and DEM Simulation - Tingting Sun; Jingnan Yang; Kuang Shi; Shufeng Lin; Jixing Yang (Advances in Civil Engineering)
Understanding the interface shear behavior between clay and structures is crucial in geotechnical engineering. The mechanism of the roughness effect in the shear process between the clay and structures was studied to reveal the macroscopic and microscopic interface shear behavior. The different surface protrusion shapes of the structures were produced using a three-dimensional (3D) printer. Direct shear tests were conducted to analyze the shear failure modes and peak and residual strengths under different conditions. Subsequently, a discrete element method (DEM) numerical analysis was employed to study the contact network, soil fabric evolution, shear zone, coordination number, and void ratio variations in the interface shear. The test results indicated that the shear interfaces exhibited the same failure mode under various conditions, and the peak and residual strengths showed a strong positive correlation with roughness. The results obtained from numerical calculations match the experimental findings. The contact orientations and principal stresses shifted during the shear process, and the shear zone, coordination number, and void ratio also showed regular changes with the change of roughness. The evolution of microscopic parameters in DEM can effectively help explain the macroscopic interface shear behavior.